Application of Project-Based Learning and Discovery Learning in Virtual Media on Analytical Thinking Skills for Animal Classification - Tunjung Nala Puti; Puguh Karyanto; Umi Fatmawati (Postgraduate, University of Mataram, 2024)
This study aims to determine the characteristics of project-based learning and discovery learning virtual media on animal classification material and test the effectiveness of project-based virtual media discovery learning on animal classification material on analytical thinking skills. This research is a mixed type of research. The research design used is the exploratory sequential design, using qualitative data analysis as the initial stage and then used as a direction to determine the formulation of research problems, samples, and quantitative data collection methods, followed by the development of virtual media instruments based on project-based learning and discovery learning. Quantitative methods are applied using quasi-experimental research. The study design used a nonrandomized control group and a pretest-posttest design. The treatment class uses PjBL-based virtual media Iimplementation, the control class uses a virtual media discovery model-based. The test instrument used is an essay question to measure analytical thinking skills adapted from Brookhart. Data analysis using ANCOVA (p = 0.05%) with prates as covariates. The result of the differences in the characteristics of project-based learning and discovery learning virtual media lies in the syntax of learning models, virtual activities, work produced, and attitudes developed. The feasibility test results of both virtual media were declared suitable for use. The results of ANCOVA showed that project-based virtual media learning is more effective in improving analytical thinking skills than discovery-based virtual media learning.